Estratégia de controle de corrente para conversor boost trifásico PFC baseado na teoria das potência instantâneas - Lapchenski, Matheus Henrique (2024)
This work presents a control strategy for a three-phase bidirectional boost PFC converter, aiming to enhance efficiency in power control within power electronics systems. The proposed method is based on the Instantaneous Power Theory, utilizing a transformation equivalent to the Park Transformation, but without the use of sinusoidal functions. Typically, solutions in this context rely on sine and cosine tables, which require significant processing time and may necessitate more expensive hardware. The technique developed in this work seeks to overcome these limitations by eliminating the need for such tables, as well as avoiding the use of PLL circuits and phase sequence identification mechanisms, providing a more efficient and simplified approach. The methodology is grounded in the theoretical development of the transformation matrix, detailing the operations and techniques employed. Computational simulations and prototype experiments were conducted to validate the method’s effectiveness. The results show a significant reduction in processing time and confirm that the objectives of this work were fully achieved.